Effect of aqueous environment on wear resistance of dental glass-ceramics - Zhenzhen Zhang; Qi Wang; Fu Wang; Ding Li; Meng Meng; Yaming Zhang; Shaofeng Zhang (BMC, 2022)
Abstract Background Wear resistance affects dental ceramics longevity and the functions of the opposing teeth. However, data for the effect of aqueous environment on wear resistance of dental ceramics are lacking. This study evaluated the effect of aqueous environment on wear resistance of typical dental glass-ceramics. Methods Disk specimens were prepared from lithium disilicate glass-ceramics (LD) and leucite reinforced glass-ceramics (LEU). The disk specimens paired with steatite antagonists were tested in a pin-on-disk tribometer under both wet and dry conditions with 10 N up to 500,000 wear cycles. The wear analysis of glass-ceramics was performed using a 3D profilometer after 100,000, 300,000 and 500,000 wear cycles. Wear morphologies were analyzed by employing scanning electron microscopy (SEM). The crystalline compositions of specimens stored in a dry environment and subsequently immersed in distilled water for 40 h were separately determined using X-ray diffraction (XRD). The chemical states of the wear surfaces for LD were analyzed by X-ray photoelectron spectroscopy (XPS). The data analysis and multiple pair-wise comparisons of means were performed by using one-way analysis of variance (ANOVA) and Tukey's post-hoc test. Results LEU in a wet environment exhibited less wear volume loss than that in a dry environment (p < 0.05). The volume loss of LD in a wet environment was higher than that in a dry environment (p < 0.05). The wear volumes of steatite antagonists paired with two glass-ceramics under dry conditions were higher than under wet conditions. Conclusions XPS spectra of LD under wet conditions indicated that high wear loss might result from the effect of stress corrosion by water and reaction of water with the ionic-covalent bonds at the crack tip. XPS spectra and SEM images of LD under dry conditions showed a possible formation of tribofilm. Within the limitations of this in vitro study, water was wear-friendly to LEU and all opposing steatites but aggravated wear for LD.